1998 diplomatic and consular directory of the Philippines. (Pasay City, Metro Manila Diplomatic Post Pub. Corp., 1998)
This directory includes Filipino and foreign diplomats who are qualified to be nominated by the public, including government and private sectors, as candidates for the selection of top diplomats. It also contains embassies and consulates accredited to the Philippines, United Nations agencies and international organizations, Department of Foreign Affairs, Philippine embassies and consulates, honorary consulates general of the Philippines, nations days, anniversaries and lastly diplomatic social usage ( a guide for U.S. representatives and families).
Through the help of this directory, the readers will have the direct link with the nominated outstanding Filipino and foreign diplomats in the year 1998. It also includes a comprehensive listing of embassies and consulates accredited to the Philippines, UN agencies and international organization and people in the Department of Foreign Affairs.
Cover title.
Earlier ed. entered under: Diplomatic & consular directory.
Keywords: Diplomatic and consular service -- Philippines -- Directories